2017
DOI: 10.1111/jhn.12478
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐centred dietetic care from the perspectives of older malnourished patients

Abstract: The quality indicators of dietetic services identified in the present study may facilitate dietitians to provide evidence-based PCC for older malnourished patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(64 citation statements)
references
References 33 publications
0
64
0
Order By: Relevance
“…Participants were mainly female (n = 178; 98.9%), with a median age of 34 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) years. Participants reported working a median of 27.5 h in dietetic-related work each week and had a median of 8 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) years of experience as a dietitian. Almost half (n = 82; 46.6%) of the participants reported that they had undergone additional training, such as postgraduate certificates/diplomas (e.g.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Participants were mainly female (n = 178; 98.9%), with a median age of 34 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) years. Participants reported working a median of 27.5 h in dietetic-related work each week and had a median of 8 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) years of experience as a dietitian. Almost half (n = 82; 46.6%) of the participants reported that they had undergone additional training, such as postgraduate certificates/diplomas (e.g.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Although various stakeholders will have differing ideas about PCC, it is important to understand patients' preferences in this regard. A recent study explored malnourished patients' views of dietetic hospital care (27) ; however, no study has explored patients' perspectives of PCC in the dietetic primary care setting (26) . Thus, the present study aimed to explore patients' experiences and perspectives of PCC in individual dietetic consultations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limitations of manual thematic analysis, there have been few previous attempts to analyse large-survey, unstructured, free-text responses in health care, including cancer services, to inform clinical and health-care practice. 7,12,15,18,19 There are notable exceptions, 14,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] but these all represent one-off analyses (see Chapter 2).…”
Section: Current Limitations In the Usefulness Of Free-text Commentsmentioning
confidence: 99%
“…et al 32 Iversen et al 27 McLemore et al 29 Hazzard et al 25 34 York et al 33 Poole et al 30 Lian et al 28 Henrich et al 26 Fradgley et al 24 Cunningham et al 22,23 Number of studies Suggestions from the survey 21 Wiseman et al 14…”
Section: Waglandmentioning
confidence: 99%
See 1 more Smart Citation